A carbonyl metal scavenger and a method for preparing the same
By constructing a hierarchical pore structure on activated carbon and the synergistic effect of nanoparticles, combined with the catalytic mechanism of Cu, Zn and Ce, the problem of carbonyl metal removal in methanol synthesis was solved, achieving a highly efficient and stable purification effect.
Patent Information
- Application Number
- CN202511261384.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-05
- Publication Date
- 2025-11-11
- Estimated Expiration
- 2045-09-05
AI Technical Summary
Existing technologies are insufficient to effectively remove trace amounts of carbonyl metal compounds during methanol synthesis, leading to catalyst deactivation and side reactions, which affect the plant's operating cycle and product quality.
Activated carbon modified with silica sol is mixed with composite oxide nanoparticles and aluminum powder to form a hierarchical pore structure. Combined with the synergistic effect of Cu(NO3)2, Zn(NO3)2 and Ce(NO3)3, carbonyl metals are deeply removed through physical adsorption and chemical catalysis.
It achieves efficient adsorption and deep decomposition of carbonyl metals, improves the stability and operating cycle of the catalyst, reduces diffusion resistance, and enhances the adsorption affinity for polar carbonyl metals.
Smart Images

Figure CN120733746B_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of chemical technology, and more specifically, to a carbonyl metal purifier and its preparation method. Background Technology
[0002] In recent years, my country's methanol industry has experienced rapid development. As a core raw material for C1 chemicals, its applications in downstream fields such as olefin production, gasoline, fuel, acetic acid, and methyl formate have continued to expand, leading to an expanding market demand. While current mainstream copper-based methanol synthesis catalysts possess high activity and selectivity, they require extremely high purity feed gas and are particularly susceptible to poisoning by carbonyl metal compounds, such as iron pentacarbonyl (Fe(CO)5) and nickel tetracarbonyl (Ni(CO)4). Even trace amounts of carbonyl metals (at the million-level) can cause irreversible deactivation of the catalyst, not only shortening the plant's operating cycle but also triggering side reactions, becoming one of the key factors restricting the performance of methanol catalysts in my country.
[0003] Existing methods for carbonyl metal removal can be divided into two categories: wet and dry methods. Wet methods include direct absorption and oxidative absorption, suitable for systems with high carbonyl iron and carbonyl nickel content, but they can only achieve coarse removal with insufficient purification precision. In dry methods, diatomaceous earth ball adsorption has limited purification depth due to weak physical adsorption; while activated carbon adsorption is widely used, conventional physical adsorption lacks selectivity for carbonyl metals. Furthermore, chemical removal methods often rely on strong oxidation reactions, which introduce byproducts and require stringent operating conditions, hindering industrial-scale application.
[0004] Patent application CN1178766A discloses a method for purifying metal carbonyl compounds in syngas, using pretreated activated carbon as the purifying agent. The pretreatment is carried out by one of the following methods: (1) acid soaking, boiling and washing with dilute acids such as HCl, HNO3 or H2SO4; (2) alkaline soaking, boiling and washing with alkaline solutions such as NaOH, KOH, Mg(OH)2, Na2CO3 or K2CO3; (3) first treating with dilute acid as described in (1), and then treating with alkaline solution as described in (2); the treated activated carbon is dried by conventional methods to obtain the purifying agent.
[0005] In this technical solution, although activated carbon can form basic functional groups containing nitrogen through alkalization, and undergo coordination chemisorption with the central metal atoms of metal carbonyl compounds, it has obvious limitations. During methanol synthesis, some basic functional groups undergo thermal decomposition due to temperature, resulting in a reduction in the number of active sites. Consequently, the adsorption capacity for metal carbonyl compounds is significantly weakened, making it difficult to stably perform the removal function. Summary of the Invention
[0006] To improve the removal efficiency of carbonyl metals from methanol feed gas, this application provides a carbonyl metal purifier and its preparation method.
[0007] In a first aspect, this application provides a method for preparing a carbonyl metal purifier, employing the following technical solution:
[0008] A method for preparing a carbonyl metal purifying agent includes the following steps:
[0009] S1: After treating activated carbon with acid, washing and drying, immerse it in a silica sol containing boric acid, ultrasonically treat and dry it, then heat it to 380~400℃ under an inert atmosphere, sinter for 120~150min, and cool it to obtain pretreated activated carbon.
[0010] S2: Cu(NO3)2 and Zn(NO3)2 are added to ethylene glycol at a mass ratio of (5~7):(2~3), followed by the addition of polyvinylpyrrolidone. The mixture is heated to 150~170℃ and reacted for 14~18h. After cooling, the solid and liquid are separated, washed, and dried. Then, under an inert atmosphere, the mixture is heated to 300~400℃ and sintered for 1.5~2.5h. After cooling, the composite oxide nanopowder is obtained.
[0011] S3: Mix pretreated activated carbon, composite oxide nanopowder, and aluminum powder in a mass ratio of (2.5~3.5):1:(0.15~0.25) until uniform, add water and knead, extrude and shape, dry, heat to 300~400℃ and sinter for 1.5~2.5h, then convert to a mixed atmosphere of reducing gas and inert gas and sinter at 160~280℃ for 4~10h, cool to obtain the final product.
[0012] In this scheme, activated carbon is modified with boric acid-containing silica sol. Boric acid promotes Si-OH condensation, forming a primary silica-oxygen network and a microporous-mesoporous hierarchical pore structure. The micropores selectively adsorb carbonyl metals, while the mesopores act as diffusion channels to transport them to the active sites, achieving adsorption-diffusion synergy. At the same time, the Si-OH groups retained in the silica-oxygen network maintain hydrophilicity and polarity, enhancing the adsorption affinity for polar carbonyl metals and significantly improving the temperature resistance of the support, ensuring the stability of the pore structure at high temperatures and guaranteeing the rapid arrival of carbonyl metals at the active sites.
[0013] The pre-synthesized composite oxide nanoparticles achieve uniform size dispersion by coordinating metal ions with the pyrrolidone groups of polyvinylpyrrolidone and using solvothermal regulation in an ethylene glycol system, thus preventing the aggregation of active sites. Simultaneously, this lays the structural foundation for the synergistic effect of subsequent active components, ensuring full exposure of active sites and effectively suppressing sintering deactivation during high-temperature reduction. The hierarchical channels of the pretreated activated carbon, the highly dispersed active sites of the composite oxide nanoparticles, and the interwoven framework formed by the aluminum powder oxidation products work synergistically to achieve efficient removal of carbonyl metals and long-term operational stability.
[0014] Preferably, in step S1, phosphoric acid with a mass concentration of 5% to 10% is used for the acid treatment.
[0015] In this scheme, phosphoric acid at this concentration can form stable bonds with the surface of activated carbon through hydroxyl groups, which can not only enhance the temperature resistance of the activated carbon skeleton and prevent structural collapse during high-temperature sintering, but also optimize the surface polarity of activated carbon, improve the physical adsorption affinity for polar carbonyl metals, strengthen the pre-adsorption capacity of the support, and lay the foundation for subsequent catalytic removal.
[0016] Preferably, in step S1, the mass concentration of boric acid in the silica sol is 3% to 5%.
[0017] In this solution, boric acid can effectively promote the formation of a primary and moderately cross-linked silica-oxygen network in silica sol, effectively balancing network integrity and pore unobstructedness, and ensuring the synergistic optimization of hierarchical pore structure and temperature resistance.
[0018] Preferably, in the mixed atmosphere, the reducing gas is hydrogen, and the volume fraction of hydrogen is 20% to 25%.
[0019] Preferably, the aluminum powder is flake-shaped aluminum powder with an aspect ratio of 10 to 20 and a particle size of 5 to 10 μm.
[0020] Preferably, in step S1, the mass concentration of nano-silica in the silica sol is 20% to 50%.
[0021] Preferably, in step S1, the particle size distribution of the nano-silica in the silica sol includes 5~10nm and 20~30nm.
[0022] Preferably, the mass ratio of the nano-silica with a particle size of 5-10 nm to the nano-silica with a particle size of 20-30 nm is (55-65):(35-45).
[0023] Preferably, in step S1, the silica sol further includes graphene oxide accounting for 0.5% to 2% of the total mass of the silica sol.
[0024] In this approach, graphene oxide can bond with Si-OH via oxygen-containing groups, enhancing the interfacial bonding force of the silicon-oxygen network and improving the mechanical strength of the support. Its layered structure also optimizes the pore distribution and forms meandering yet continuous mesoporous channels, improving adsorption contact efficiency while maintaining the diffusion rate. Simultaneously, the conductivity of graphene oxide promotes electron transfer to active sites, accelerating the activation and breakage of MC bonds and enhancing catalytic efficiency.
[0025] Preferably, the mass ratio of the polyvinylpyrrolidone to the total mass of Cu(NO3)2 and Zn(NO3)2 is (0.15~0.25):1.
[0026] Preferably, in step S2, the temperature is raised to 150~170℃, and after reacting for 14~18h, it is cooled to 75~80℃, and Ce(NO3)3 and oxalic acid are added and mixed for 2~2.5h.
[0027] Preferably, the mass ratio of Ce(NO3)3 to oxalic acid is 1:(0.4~0.42).
[0028] In this scheme, the introduction of Ce(NO3)3 and oxalic acid can form a cerium oxalate complex, which inhibits the growth of CeO2 grains through molecular-level spatial confinement, resulting in small-sized, highly dispersed CeO2. Simultaneously, the CeO2 generated after the decomposition of the complex is facilitated by Zn... 2+ The structural isolation effect regulates the generation site of oxygen vacancies, providing stable surface active sites for the activation of carbonyl metals. The oxygen vacancies on the surface act as strong Lewis acid centers, polarizing the MC bonds of carbonyl metals and synergistically promoting the removal of carbonyl metals by active sites.
[0029] Preferably, the total mass ratio of Cu(NO3)2 and Zn(NO3)2 to Ce(NO3)3 is 8.5:(0.8~1.2).
[0030] Preferably, in step S3, before adding water and kneading, an ammonium phosphomolybdate solution is added, wherein the mass ratio of ammonium phosphomolybdate to composite oxide nanoparticles in the ammonium phosphomolybdate solution is (0.03~0.05):1.
[0031] Preferably, the ammonium phosphomolybdate ammonia solution comprises ammonium phosphomolybdate and ammonia water, wherein the mass concentration of the ammonium phosphomolybdate is 15% to 25%.
[0032] In this scheme, ammonium phosphomolybdate achieves molecular-level uniform dispersion through the dissolution effect of ammonia water, forming a thin and uniform coating layer on the surface of the composite oxide nanoparticles. The polar groups retained in the coating layer enhance the selective physical adsorption of polar carbonyl metals. On the other hand, the thin coating layer ensures sufficient exposure of the active sites, providing a sufficient active interface for the catalytic decomposition of carbonyl metals. This not only enhances the adsorption capacity for carbonyl metals but also improves the catalytic decomposition rate, ultimately achieving an increase in carbonyl iron capacity and a prolonged breakthrough time.
[0033] Secondly, this application also provides a carbonyl metal purifier prepared by the above-described preparation method.
[0034] In summary, this application has the following beneficial effects:
[0035] 1. This application utilizes boric acid to promote silica sol condensation, constructing a primary silica-oxygen network on the surface of activated carbon. This improves the structural temperature resistance and reduces the probability of high-temperature pore collapse, forming a microporous-mesoporous hierarchical pore system. Simultaneously, it retains some polar groups to achieve selective physical adsorption of carbonyl metals, reducing diffusion resistance. In the preparation of composite oxide nanopowders, in-situ nano-sizing is employed, based on the structural isolation of zinc oxide, to block subsequent Cu... 0 The high-temperature migration path of particles inhibits aggregation and ensures the quantity and uniform dispersion of subsequent active sites, thereby effectively catalyzing the decomposition of carbonyl metals into gaseous CO and metal deposition, achieving in-situ regeneration.
[0036] 2. In this application, CeO2 and ZnO-Cu are preferred. 0 The ternary composite structure exhibits a bifunctional synergistic catalytic mechanism involving electron-acid sites: ZnO nanophase acts as a physical separator, effectively blocking the reaction between CeO2 and Cu. 0 The migration and aggregation of particles at high temperatures simultaneously lock oxygen vacancies onto active sites on the CeO2 surface, maintaining its acid-site catalytic function; oxygen vacancies on the CeO2 surface polarize the MC bond, Cu 0 Simultaneous activation of CO bonds in carbonyl metals weakens bond energy and synergistically catalyzes carbonyl metal decomposition, achieving deep decomposition and long-term removal of carbonyl metals. Attached Figure Description
[0037] Figure 1 The XRD patterns of the purified agent products in Examples 1-3 are shown below.
[0038] Figure 2 Here is a SEM image of the purifying agent to be reduced in Example 3;
[0039] Figure 3 This is a SEM image of the finished purifying agent from Example 3. Detailed Implementation
[0040] The present application will be further described in detail below with reference to the embodiments.
[0041] Unless otherwise specified, the raw materials used in the embodiments and comparative examples of this application are all commercially available.
[0042] The purifying agent prepared in this application is preferably used after fine desulfurization;
[0043] The molecular weight of polyvinylpyrrolidone is 40,000;
[0044] Activated carbon, specific surface area 1100 m² 2 / g, bulk density 480kg / m³ 3 The average aperture is 20 Å.
[0045] Example 1
[0046] The preparation method of the carbonyl metal purifier in this embodiment includes the following steps:
[0047] S1: Immerse 30g of activated carbon in 300mL of 8% phosphoric acid solution, heat to 80℃, stir and mix for 2h, centrifuge, wash with deionized water until neutral, transfer to a drying oven, dry at 80℃ to constant weight, then immerse in 150mL of silica sol containing boric acid, transfer to an ultrasonic device, ultrasonically treat for 30min at 40kHz and 200W, centrifuge, transfer to a drying oven, dry at 80℃ to constant weight, then sinter at 390℃ for 140min under nitrogen atmosphere at a rate of 3℃ / min, and naturally cool to room temperature to obtain pretreated activated carbon;
[0048] S2: Add 18g Cu(NO3)2 and 7.5g Zn(NO3)2 to 300mL ethylene glycol, stir and mix evenly, then add 5.1g polyvinylpyrrolidone, stir and mix evenly, slowly heat to 160℃, reflux for 16h, cool to room temperature, centrifuge, wash 3 times with anhydrous ethanol, transfer to a drying oven, dry at 80℃ to constant weight, then sinter at 3℃ / min to 350℃ under nitrogen atmosphere for 2h, and naturally cool to room temperature to obtain composite oxide nanopowder;
[0049] S3: Mix 18g of pretreated activated carbon, 6g of composite oxide nanopowder, and 1.2g of aluminum powder evenly, add 30mL of deionized water, knead for 15min, and then extrude the mixture into a cylinder with a diameter of 3.0mm × 3.0mm using a mold. Transfer the cylinder to a drying oven and dry it at 80℃ to constant weight. In an air atmosphere, heat the mixture to 350℃ at a rate of 3℃ / min and sinter for 2h. Then switch to a mixed atmosphere of hydrogen and nitrogen (volume ratio of hydrogen to nitrogen is 1:4), adjust the temperature to 220℃, and sinter for 6h. Allow the mixture to cool naturally to room temperature to obtain the finished purification agent.
[0050] The silica sol contains 4% boric acid and 35% nano-silica, with a particle size distribution of 5-10 nm and 20-30 nm. The mass ratio of nano-silica with a particle size of 5-10 nm to that with a particle size of 20-30 nm is 6:4. The aluminum powder is in the form of flakes with an aspect ratio of 10-20 and a particle size of 5-10 μm.
[0051] Example 2
[0052] The preparation method of the carbonyl metal purifier in this embodiment includes the following steps:
[0053] S1: Immerse 30g of activated carbon in 300mL of 5% phosphoric acid solution, heat to 90℃, stir and mix for 2.5h, centrifuge, wash with deionized water until neutral, transfer to a drying oven, dry at 80℃ to constant weight, then immerse in 150mL of silica sol containing boric acid, transfer to an ultrasonic device, ultrasonically treat for 30min at 40kHz and 200W, centrifuge, transfer to a drying oven, dry at 80℃ to constant weight, then sinter at 380℃ for 150min under nitrogen atmosphere at a rate of 3℃ / min, and cool naturally to room temperature to obtain pretreated activated carbon;
[0054] S2: Add 15g Cu(NO3)2 and 6g Zn(NO3)2 to 300mL ethylene glycol, stir and mix evenly, then add 3.15g polyvinylpyrrolidone, stir and mix evenly, slowly heat to 150℃, reflux for 18h, cool to room temperature, centrifuge, wash 3 times with anhydrous ethanol, transfer to a drying oven, dry at 80℃ to constant weight, then sinter at 3℃ / min to 300℃ under nitrogen atmosphere for 2.5h, and naturally cool to room temperature to obtain composite oxide nanopowder;
[0055] S3: Mix 15g of pretreated activated carbon, 6g of composite oxide nanopowder, and 0.9g of aluminum powder evenly, add 24mL of deionized water, knead for 15min, and then extrude the mixture into a Φ3.0mm×3.0mm cylinder using a mold. Transfer the cylinder to a drying oven and dry it at 80℃ to constant weight. In an air atmosphere, heat the mixture to 280℃ at 3℃ / min and sinter for 2.5h. Then switch to a mixed atmosphere of hydrogen and nitrogen (volume ratio of hydrogen to nitrogen is 1:4), adjust the temperature to 160℃, and sinter for 10h. Allow the mixture to cool naturally to room temperature to obtain the finished purification agent.
[0056] The silica sol contains 3% boric acid and 20% nano-silica, with a particle size distribution of 5-10 nm and 20-30 nm. The mass ratio of nano-silica with a particle size of 5-10 nm to that with a particle size of 20-30 nm is 5.5:4.5. The aluminum powder is in the form of flakes with an aspect ratio of 10-20 and a particle size of 5-10 μm.
[0057] Example 3
[0058] The preparation method of the carbonyl metal purifier in this embodiment includes the following steps:
[0059] S1: Immerse 30g of activated carbon in 300mL of 10% phosphoric acid solution, heat to 75℃, stir and mix for 1.5h, centrifuge, wash with deionized water until neutral, transfer to a drying oven, dry at 80℃ to constant weight, then immerse in 150mL of silica sol containing boric acid, transfer to an ultrasonic device, ultrasonically treat for 30min at 40kHz and 200W, centrifuge, transfer to a drying oven, dry at 80℃ to constant weight, then sinter at 400℃ for 120min under nitrogen atmosphere at a rate of 3℃ / min, and cool naturally to room temperature to obtain pretreated activated carbon;
[0060] S2: Add 21g Cu(NO3)2 and 9g Zn(NO3)2 to 300mL ethylene glycol, stir and mix evenly, then add 2.5g polyvinylpyrrolidone, stir and mix evenly, slowly heat to 170℃, reflux for 14h, cool to room temperature, centrifuge, wash 3 times with anhydrous ethanol, transfer to a drying oven, dry at 80℃ to constant weight, then sinter at 400℃ for 1.5h under nitrogen atmosphere, and naturally cool to room temperature to obtain composite oxide nanopowder;
[0061] S3: Mix 21g of pretreated activated carbon, 6g of composite oxide nanopowder, and 1.5g of aluminum powder evenly, add 39mL of deionized water, knead for 20min, and then extrude the mixture into a Φ3.0mm×3.0mm cylinder using a mold. Transfer the cylinder to a drying oven and dry it at 80℃ to constant weight. In an air atmosphere, heat the cylinder to 400℃ at 3℃ / min and sinter for 1.5h. Allow it to cool naturally to room temperature to obtain the purification agent to be reduced. Then switch to a mixed atmosphere of hydrogen and nitrogen (volume ratio of hydrogen to nitrogen is 1:3), adjust the temperature to 280℃, sinter for 4h, and allow it to cool naturally to room temperature to obtain the finished purification agent.
[0062] The silica sol contains 5% boric acid and 50% nano-silica, with a particle size distribution of 5-10 nm and 20-30 nm. The mass ratio of nano-silica with a particle size of 5-10 nm to that with a particle size of 20-30 nm is 6.5:3.5. The aluminum powder is in the form of flakes with an aspect ratio of 10-20 and a particle size of 5-10 μm.
[0063] Example 4
[0064] The difference between this embodiment and Embodiment 1 is that:
[0065] In step S1, the silica sol also includes graphene oxide accounting for 0.5% of the total mass of the silica sol.
[0066] Before use, the silica sol is pre-transferred into an ultrasonic device and ultrasonically treated for 20 minutes at 40 kHz and 200 W.
[0067] Everything else is the same as in Example 1.
[0068] Example 5
[0069] The difference between this embodiment and embodiment 4 is that:
[0070] In step S1, the silica sol also includes graphene oxide accounting for 2% of the total mass of the silica sol.
[0071] Before use, the silica sol is pre-transferred into an ultrasonic device and ultrasonically treated for 30 minutes at 40 kHz and 200 W.
[0072] The rest is the same as in Example 4.
[0073] Example 6
[0074] The difference between this embodiment and embodiment 5 is as follows:
[0075] In step S1, the silica sol also includes graphene oxide accounting for 1.5% of the total mass of the silica sol.
[0076] Before use, the silica sol is pre-transferred into an ultrasonic device and ultrasonically treated for 25 minutes at 40 kHz and 200 W.
[0077] Step S2 is as follows: 18g Cu(NO3)2 and 7.5g Zn(NO3)2 are added to 300mL ethylene glycol and stirred until homogeneous. Then, 5.1g polyvinylpyrrolidone is added and stirred until homogeneous. The mixture is slowly heated to 170℃ and refluxed for 14h. After cooling to 80℃, 2.4g Ce(NO3)3 and 0.96g oxalic acid are added. The mixture is kept at 80℃ and stirred for 2h. After cooling to room temperature, the mixture is centrifuged and washed three times with anhydrous ethanol. The mixture is then transferred to a drying oven and dried at 80℃ to constant weight. Finally, under a nitrogen atmosphere, the temperature is increased to 350℃ at 3℃ / min and sintered for 2h. After naturally cooling to room temperature, composite oxide nanopowder is obtained.
[0078] The rest is the same as in Example 5.
[0079] Example 7
[0080] The difference between this embodiment and embodiment 6 is that:
[0081] Step S2 is as follows: 18g Cu(NO3)2 and 7.5g Zn(NO3)2 are added to 300mL ethylene glycol and stirred until homogeneous. Then, 5.1g polyvinylpyrrolidone is added and stirred until homogeneous. The mixture is slowly heated to 150℃ and refluxed for 18h. After cooling to 75℃, 3.6g Ce(NO3)3 and 1.50g oxalic acid are added. The mixture is kept at 75℃ and stirred for 2.5h. After cooling to room temperature, the mixture is centrifuged and washed three times with anhydrous ethanol. The mixture is then transferred to a drying oven and dried at 80℃ to constant weight. Under a nitrogen atmosphere, the temperature is increased to 350℃ at 3℃ / min and sintered for 2h. After naturally cooling to room temperature, composite oxide nanopowder is obtained.
[0082] Step S3 is as follows: Mix 18g of pretreated activated carbon, 6g of composite oxide nanopowder, and 1.2g of aluminum powder evenly, then add ammonium phosphomolybdate solution and mix evenly. Add 30mL of deionized water, knead for 15min, and then extrude it into cylindrical strips of Φ3.0mm×3.0mm using a mold. Transfer the strips to a drying oven and dry them at 80℃ to constant weight. In an air atmosphere, heat the strips to 350℃ at 3℃ / min and sinter for 2h. Then switch to a mixed atmosphere of hydrogen and nitrogen (volume ratio of hydrogen to nitrogen is 1:4), adjust the temperature to 220℃, and sinter for 6h. Allow the strips to cool naturally to room temperature to obtain the finished purification agent.
[0083] The preparation steps for ammonium phosphomolybdate ammonia solution are as follows:
[0084] Add 0.18g of ammonium phosphomolybdate to 1.02g of ammonia water with a mass concentration of 5%, stir and mix evenly to obtain the final product.
[0085] All of the above-mentioned ammonium phosphomolybdate solution was added.
[0086] The rest is the same as in Example 6.
[0087] Example 8
[0088] The difference between this embodiment and embodiment 7 is that:
[0089] The preparation steps for ammonium phosphomolybdate ammonia solution are as follows:
[0090] Add 0.3g of ammonium phosphomolybdate to 0.9g of ammonia water with a mass concentration of 5%, stir and mix evenly to obtain the final product.
[0091] All of the above-mentioned ammonium phosphomolybdate solution was added.
[0092] The rest is the same as in Example 7.
[0093] Comparative Example 1
[0094] The difference between this comparative example and Example 1 is as follows:
[0095] S2: Add 7.65g CuO and 3.21g ZnO to 300mL ethylene glycol, transfer to an ultrasonic device, sonicate at 40kHz and 200W for 20min, add 5.1g polyvinylpyrrolidone, stir and mix evenly, slowly heat to 160℃, reflux for 16h, cool to room temperature, centrifuge, wash 3 times with anhydrous ethanol, transfer to a drying oven, dry at 80℃ to constant weight, then sinter at 3℃ / min to 350℃ under nitrogen atmosphere for 2h, and naturally cool to room temperature to obtain composite oxide nanopowder;
[0096] The particle size distribution of CuO and ZnO is 10~50nm, and the amount of both is calculated based on the equimolar conversion of the amount of Cu(NO3)2 and Zn(NO3)2 in Example 1.
[0097] Everything else is the same as in Example 1.
[0098] Comparative Example 2
[0099] The difference between this comparative example and Example 1 is as follows:
[0100] S1: Immerse 30g of activated carbon in 300mL of 8% phosphoric acid solution, heat to 80℃, stir and mix for 2h, centrifuge, wash with deionized water until neutral, transfer to a drying oven, dry at 80℃ to constant weight, and obtain pretreated activated carbon.
[0101] Everything else is the same as in Example 1.
[0102] Comparative Example 3
[0103] The difference between this comparative example and Example 1 is as follows:
[0104] S1: Immerse 30g of activated carbon in 100mL of 8% phosphoric acid solution, heat to 80℃, stir and mix for 2h, centrifuge, wash with deionized water until neutral, transfer to a drying oven, dry at 80℃ to constant weight, then immerse in 150mL of silica sol, transfer to an ultrasonic device, ultrasonically treat for 30min at 40kHz and 200W, centrifuge, transfer to a drying oven, dry at 80℃ to constant weight, then sinter at 390℃ for 140min under nitrogen atmosphere at a rate of 3℃ / min, and cool naturally to room temperature to obtain pretreated activated carbon;
[0105] Silica sol does not contain boric acid.
[0106] Everything else is the same as in Example 1.
[0107] Comparative Example 4
[0108] The difference between this comparative example and Example 1 is as follows:
[0109] S3: Mix 18g of pretreated activated carbon, 6g of composite oxide nanopowder, and 1.2g of aluminum powder evenly, add 30mL of deionized water, knead for 15min, then extrude into cylindrical strips of Φ3.0mm×3.0mm using a mold, transfer to a drying oven, dry at 80℃ to constant weight, sinter in air at 3℃ / min to 350℃ for 2h, and then cool naturally to room temperature to obtain the finished purification agent.
[0110] Everything else is the same as in Example 1.
[0111] Performance testing
[0112] Under a nitrogen atmosphere, the purified agent products prepared in Examples 1-8 and Comparative Examples 1-4 were loaded into a reaction tube (inner diameter 30 mm, wall thickness 1.5 mm, length 600 mm) at their original particle size. Both ends were pre-filled with quartz wool. The filling volume of the purified agent was 33 mL. The tube wall was tapped while filling to ensure uniform and compaction. After filling, the top was covered with 5 mm thick quartz wool for fixation. The height-to-diameter ratio of the bed was 2.0. Then, the reaction tube was connected to the gas circuit system, high-purity nitrogen was introduced, and the pressure was adjusted to 0.2 MPa. The pressure was maintained for 30 minutes. A pressure drop of <0.005 MPa was considered a leak test result.
[0113] After the leak test is passed, a mixture of H2 / N2 gas (volume ratio of 45:55) is introduced, and the temperature is increased to 150℃ at a rate of 2℃ / min and maintained for 10 hours. Then, nitrogen gas is switched and the mixture is purged for 30 minutes. Finally, a feed gas containing Fe(CO)5 (n) is introduced. H2 and n CO =50:50), where the inlet concentration of Fe(CO)5 is controlled at 50 ppm, the temperature is adjusted to 180℃, the pressure of the reaction system is 0.1 MPa, and the flow rate is adjusted to a space velocity of 5000 h⁻¹. -1 After stabilization for 1 hour, inlet and outlet concentration monitoring was initiated using gas chromatography with an electron capture detector. Initially, monitoring was performed every 2 hours. If the outlet iron pentacarbonyl concentration was ≥0.05 ppb, monitoring was changed to every 15 minutes. If the outlet iron pentacarbonyl concentration exceeded 0.1 ppb three times consecutively and showed an upward trend, it was considered that the purifier had been penetrated by iron pentacarbonyl. The penetration time t was recorded, and the true iron pentacarbonyl capacity (i.e., the mass of Fe(CO)5 adsorbed by the purifier relative to the mass of the purifier itself) was calculated. The feed gas was immediately cut off, high-purity nitrogen was introduced, and the reaction tube was purged for 30 minutes. The temperature was then lowered to room temperature. The test results are shown in Table 1. Based on GB / T 31590-2015, the compressive strength of a single granule of the finished purifier was tested. The test results are shown in Table 1.
[0114] Table 1. Performance test data of the purifying agents obtained in Examples 1-8 and Comparative Examples 1-4
[0115]
[0116] Combining Table 1 and Figures 1-3 The analysis is as follows:
[0117] As shown in Examples 1-3 and Comparative Examples 1-4, the composite oxide nanopowder prepared in advance by the solvothermal method achieves uniform nanoscale dispersion of the active components, significantly exposing catalytic and adsorption active sites (such as metal centers and polar groups), laying the foundation for the physical adsorption and catalytic decomposition of pentacarbonyl iron, and directly improving the carbonyl iron capacity and breakthrough time. When activated carbon is modified with boric acid-containing silica sol, boric acid promotes the condensation of silica sol to form a primary silicon-oxygen network, optimizing the structure and mass transfer; hydrogen reduction, as the core step, is... Figure 1 It can be seen that as the reduction temperature increases from 160℃ (Example 2) to 220℃ (Example 1) and then to 280℃ (Example 3), the diffraction intensity of the (111) crystal plane of metallic Cu shows an increasing trend, indicating that zero-valent copper (Cu) 0 The content of ) increases with increasing temperature. Especially at 280℃, the combination Figure 2 and Figure 3 It can be seen that the purifying agent to be reduced in Example 3 ( Figure 2 Due to the evaporation of moisture and the decomposition of components, many pores formed on the surface. The purifying agent product in Example 3 (… Figure 3 The grain size became significantly smaller and more uniformly dispersed, with an increase in micropores, indicating that at 280℃, deep reduction generated a high concentration of zero-valent copper without inducing grain agglomeration, ultimately achieving physical adsorption and chemical catalysis (Cu). 0 Synergistic effect of the 111 crystal plane.
[0118] Based on this, Examples 4-8 demonstrate that: by adding graphene oxide to silica sol, the combination of its two-dimensional structure and the silicon-oxygen network enhances the structural stability of the carrier and optimizes pore mass transfer, thereby improving purification performance; furthermore, by optimizing the amount of graphene oxide and introducing cerium oxide, the catalytic decomposition ability of iron pentacarbonyl is effectively enhanced, forming a synergistic effect with the pore optimization of graphene oxide, resulting in continuous performance improvement. Subsequently, the introduction of ammonium phosphomolybdate enhances the selective adsorption of polar iron pentacarbonyl, synergistically improving the adsorption capacity and purification persistence of the purifier for iron pentacarbonyl in conjunction with the structural support of graphene oxide and the catalytic effect of cerium oxide.
[0119] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.
Claims
1. A method for preparing a carbonyl metal purifying agent, characterized in that, Includes the following steps: S1: After treating activated carbon with acid, washing and drying, immersing it in a silica sol containing boric acid, ultrasonically treating and drying it, then heating it to 380~400℃ under an inert atmosphere and sintering it for 120~150 min, and cooling it, the pretreated activated carbon is obtained; the acid treatment uses phosphoric acid with a mass concentration of 5%~10%; S2: Cu(NO3)2 and Zn(NO3)2 are added to ethylene glycol at a mass ratio of (5~7):(2~3), followed by the addition of polyvinylpyrrolidone. The mixture is heated to 150~170℃ and reacted for 14~18h. After cooling, the solid and liquid are separated, washed, and dried. Then, under an inert atmosphere, the mixture is heated to 300~400℃ and sintered for 1.5~2.5h. After cooling, the composite oxide nanopowder is obtained. S3: Mix pretreated activated carbon, composite oxide nanopowder, and aluminum powder in a mass ratio of (2.5~3.5):1:(0.15~0.25) until uniform, add water and knead, extrude and shape, dry, heat to 300~400℃ and sinter for 1.5~2.5h, then convert to a mixed atmosphere of reducing gas and inert gas and sinter at 160~280℃ for 4~10h, cool to obtain the final product.
2. The method for preparing the carbonyl metal purifier according to claim 1, characterized in that, In step S1, the mass concentration of boric acid in the silica sol is 3%~5%.
3. The method for preparing the carbonyl metal purifier according to claim 1, characterized in that, In the mixed atmosphere, the reducing gas is hydrogen, and the volume fraction of hydrogen is 20%~25%.
4. The method for preparing the carbonyl metal purifier according to claim 1, characterized in that, In step S1, the silica sol also includes graphene oxide accounting for 0.5% to 2% of the total mass of the silica sol.
5. The method for preparing the carbonyl metal purifier according to claim 1, characterized in that, In step S2, the temperature is raised to 150~170℃, and after reacting for 14~18h, it is cooled to 75~80℃, and Ce(NO3)3 and oxalic acid are added and mixed for 2~2.5h.
6. The method for preparing the carbonyl metal purifier according to claim 5, characterized in that, The total mass ratio of Cu(NO3)2 and Zn(NO3)2 to Ce(NO3)3 is 8.5:(0.8~1.2).
7. The method for preparing the carbonyl metal purifier according to claim 5, characterized in that, The mass ratio of Ce(NO3)3 to oxalic acid is 1:(0.4~0.42).
8. The method for preparing the carbonyl metal purifier according to claim 1, characterized in that, In step S3, before adding water and kneading, an ammonium phosphomolybdate solution is added, wherein the mass ratio of ammonium phosphomolybdate to composite oxide nanoparticles in the ammonium phosphomolybdate solution is (0.03~0.05):
1.
9. The method for preparing the carbonyl metal purifier according to claim 8, characterized in that, The ammonium phosphomolybdate ammonia solution comprises ammonium phosphomolybdate and ammonia water, wherein the mass concentration of ammonium phosphomolybdate is 15%~25%.
10. A carbonyl metal purifier prepared by the method of any one of claims 1 to 9.
Citation Information
Patent Citations
Purifying method for metal carbonyl compound in synthetic gas
CN1178766A
Hydrogenation mercaptan-removal catalyst and its preparation method and use
CN102451693A
Cleaning agent for removing iron carbonyl and nickel carbonyl in synthesis gas and preparation method and application of cleaning agent
CN102814160A